Search found 1 match

Return to advanced search

Induction: have a working Proof but first step (n=1) fails  TOPIC_SOLVED

I am needing to prove the following by induction: {n} {\sum } {\rm }{\rm } 2^{n -1}{\rm } =1+2+2^{2}+...+2^{n -1}=2^{n } {j =0} My proof is like so: A ssumption: 2^{(k-1)} = 2^{k} P roof needed: 2^{(k-1)} + 2^{(k+1-1)} = 2^{(k+1)} Using A ssumption, Added 2^(k+1-1) to...
by corgan
on Thu Dec 12, 2013 4:51 am
 
Forum: Advanced Algebra ("pre-calculus")
Topic: Induction: have a working Proof but first step (n=1) fails
Replies: 1
Views: 712

Return to advanced search